Modulation of Cognition: The Role of Gnidia glauca on Spatial Learning and Memory Retention in High-Fat Diet-Induced Obese Rats - Wycliffe Makori Arika; Cromwell Mwiti Kibiti; Joan Murugi Njagi; Mathew Piero Ngugi (Neural Plasticity)
Chronic exposures to high-fat diets are linked to neuropathological changes that culminate in obesity-related cognitive dysfunction and brain alteration. Learning, memory performance, and executive function are the main domains affected by an obesogenic diet. There are limited effective therapies for addressing cognitive deficits. Thus, it is important to identify additional and alternative therapies. In African traditional medicine, Gnidia glauca has putative efficacy in the management of obesity and associated complications. The use of Gnidia glauca is largely based on its long-term traditional use. Its therapeutic application has not been accompanied by sufficient scientific evaluation to validate its use. Therefore, the current study sought to explore the modulatory effects of dichloromethane leaf extracts of Gnidia glauca on cognitive function in the high-fat diet- (HFD-) induced obese rats. Obesity was induced by feeding the rats with prepared HFD and water ad libitum for 6 weeks. The in vivo antiobesity effects were determined by oral administration of G. glauca at dosage levels of 200, 250, and 300 mg/kg body weight in HFD-induced obese rats from the 6th to the 12th weeks. The Lee obesity index was used as a diagnostic criterion of obesity. The Morris water maze was employed to test spatial learning and memory retention in rats. The results indicated that Gnidia glauca showed potent antiobesity effects as indicated in the reduction of body weight and obesity index in extract-treated rats. Moreover, Gnidia glauca exhibited cognitive-enhancing effects in obese rats. The positive influences on cognitive functions might be attributed to the extracts’ phytochemicals that have been suggested to confer protection against obesity-induced oxidative damage, reduction of central inflammation, and increased neurogenesis. The therapeutic effects observed suggest that Gnidia glauca might be an alternative to current medications for the symptomatic complications of obesity, such as learning and memory loss. Further studies are therefore needed to establish its toxicity profiles.